Examining the Impact of Mobile-Based Extramural Activities on Vocabulary Development among EFL Learners: A Mixed-Methods Investigation - Jahangeer, Muhammad; Naz, Samina; Raheem, Muhammad Arslan (Annals of Human and Social Sciences, 2024)
The main objective of this research was to investigate the effect of Extramural English exercises on developing word-stock in higher secondary school EFL students using a mixed-methods methodology. From two language learning schools, 48 participants were eligible and willing to participate, twenty-four were male students, while twenty-four were females. Vocabulary development was assessed through pre- and post-tests. Semi-structured interview enabled us to explore all aspects of participants’ inclination and attitude towards EE-based exercise. The experimental group’s results showed that the activities that are based on Extramural English have a significant impact on improvement in learners’ vocabulary acquisition (p<0.001). Furthermore the findings indicated, in female and male learners, there were no discernible variations in the word knowledge ensuing EE exercise (p=0.27). Research indicates that participants preferred a variety of mobile-based EE activities that helped them expand their vocabulary. In light of these conclusions, the research suggests that teachers should successfully incorporate mobile technology into language instruction to boost students’ language skills.